Protective Effects of Deferoxamine on Vestibulotoxicity in Gentamicin-Induced Bilateral Vestibulopathy Rat Model - Kim, Hyo-Jung; Lee, Jin-Ok; Kim, Ji-Soo (Frontiers in Neurology, 2021)
Introduction: Administration of aminoglycoside (AG) antibiotics is one of the most common causes of ototoxicity. This study aimed to determine the protective effects of deferoxamine, an iron-chelating agent, on vestibulotoxicity using an intratympanic gentamicin injection (ITGM)-induced bilateral vestibulopathy rat model. Methods: Fifteen Sprague-Dawley rats were randomly assigned to the ITGM only (n = 5), the ITGM combined with intramuscular deferoxamine (DFO) injection (ITGM+DFO, n = 5), or the intratympanic normal saline (control, n = 5) group. The rats in the ITGM+DFO group received intramuscular injection of 150 mg/kg of deferoxamine at 30, 90, and 150 min after the ITGM. The vestibular function was evaluated using the rotarod and open field test every 3 days after the injection until Day 16 when the rats were subjected to histological changes. Results: The rats in the ITGM only group began to show significantly impaired vestibular function 2 days after ITGM into both ears. In contrast, the vestibular function was maintained in the control and ITGM+DFO groups without a difference throughout the experiments. The rats in the ITGM only group showed a near-complete loss of the type I and II hair cells and a collapse of the sensory epithelium in both the saccule and utricle. In contrast, the rats in the ITGM+DFO and control groups showed a relatively well-preserved sensory epithelium including the hair cells, cilia, and otolith layer. Conclusion: This study provides experimental evidence for preventive effects of iron-chelating agents on AG-induced vestibulotoxicity. Simultaneous administration of iron-chelating agents may be considered when using ototoxic agents, especially in those considered to be vulnerable to toxic damage of the inner ear.